Peran Pendidikan Agama Islam Dalam Membangun Generasi Emas Berkarakter Unggul - Husyaini, Rindhy; Youlanda, Puspa Novia; Damanik, Muhammad Zein (TARBIYAH: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
This study aims to examine the role of Islamic Religious Education in building a golden generation with superior character. The golden generation is a generation that is able to bring about improvements in the life of the nation to become a dignified, harmonious, and quality nation and a generation that has a greater productive age. This study uses a qualitative method using literature study analysis, which analyzes various literature and relevant sources regarding the role of Islamic Religious Education in building a golden generation with superior character. The results of the study show that Islamic Religious Education has an equally important role in forming a golden generation with superior character, among its roles as a moral and ethical foundation, understanding of Islamic teachings, developing spiritual awareness, forming noble morals, introducing good and bad values, preventing negative behavior, strengthening Islamic identity, developing moral independence, developing social and humanitarian understanding.